2015
DOI: 10.1177/0363546515596409
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Loop Double Endobutton Reconstruction for Acromioclavicular Joint Dislocation

Abstract: Background: Current anatomic methods for reconstruction of the dislocated acromioclavicular (AC) joint show improved clinical results but continue to be associated with significant rates of fixation loss and complications, limiting more widespread use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 53 publications
7
80
0
Order By: Relevance
“…Some studies have demonstrated higher clinical success rates and superior biomechanical outcomes when CC ligament reconstruction has been compared with other techniques 1 - 5 . However, the detailed operative techniques, complication rates, and follow-up periods have differed among studies 6 - 13 . To our knowledge, the longest mean duration of follow-up for this procedure was 5.2 years, as reported by Struhl and Wolfson 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated higher clinical success rates and superior biomechanical outcomes when CC ligament reconstruction has been compared with other techniques 1 - 5 . However, the detailed operative techniques, complication rates, and follow-up periods have differed among studies 6 - 13 . To our knowledge, the longest mean duration of follow-up for this procedure was 5.2 years, as reported by Struhl and Wolfson 6 .…”
mentioning
confidence: 99%
“…However, the detailed operative techniques, complication rates, and follow-up periods have differed among studies 6 - 13 . To our knowledge, the longest mean duration of follow-up for this procedure was 5.2 years, as reported by Struhl and Wolfson 6 . The long-term (>10-year) clinical and radiographic outcomes of this procedure remain uncertain 6 - 13 .…”
mentioning
confidence: 99%
“…Arthroscopy-assisted reconstruction of the CC ligament by endobutton fixation proved a safe and easy way for the treatment of AC joint dislocation, which can provide reliable fixation, a fast recovery and cause less trauma [8]. The continuous loop device can eliminate the possibility of knot breakage or slippage, and MRI suggested a robust healing response, which can be recommended both for chronic and acute dislocations [9]. Although the use of double endobutton plate technique for the treatment of Rockwood III-VI dislocations has been widely recognized, the improvement of the double endobutton technique has never stopped [8,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The continuous loop device can eliminate the possibility of knot breakage or slippage, and MRI suggested a robust healing response, which can be recommended both for chronic and acute dislocations [9]. Although the use of double endobutton plate technique for the treatment of Rockwood III-VI dislocations has been widely recognized, the improvement of the double endobutton technique has never stopped [8,9,10]. According to reset requirement during operation, our novel double endobutton can adjust loop length for satisfying different individual operative methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation